Indigenous Readings: Ethics, Politics, and Method in Indigenous Studies on Turtle Island and Beyond - Benkhadda, Angela Maria (Current Objectives of Postgraduate American Studies, 2023)
Reading has been at the center of ongoing debates among scholars of Native American, First Nations, Métis, and Inuit literatures for decades. In the context of these debates, my paper seeks to address the difficulties and challenges of reading Indigenous literatures from the standpoint of emerging non-Indigenous scholars educated in a Euro-American framework. For this purpose, the paper provides a toolbox of questions and strategies—organized around the five broad and interrelated topics of positionality, relationality, ethics, context, and incomplete readings—that can help students and early-career scholars to critically question their reading practices. To this end, my paper synthesizes a variety of scholarly perspectives on politics, ethics, and methods in Indigenous studies and applies the resulting framework to Leslie Marmon Silko’s opening of her novel Ceremony “(1977).